Negative Politeness Strategies Applied in the Movie Charlie’s Angels 2019 - Yolanda, Thalia; Udayana, I Nyoman; Mulyana, Novita (Devotion : Journal of Research and Community Service, 2022)
This research is a pragmatic study of the use of negative politeness strategies. This study aims to identify negative politeness strategies used by characters in films and to analyze why characters in films use negative politeness strategies in their speech. This study will use a qualitative method in utilizing the study of negative politeness strategies by describing the problem as clearly as possible. The data will be taken from a film called Charlie's Angels 2019. The theory that will be used in this research is the theory proposed by Brown and Levinson's negative politeness strategy in 1992. The results of this study conclude that there are ten strategies proposed by Brown and Levinson as a way to direct, does not assume or presuppose, and does not force and fulfill the other wishes of the listener. The negative politeness strategy has several sub-strategies that have different goals. They use strategies related to the context of the conversation and the situation.